C5-Azobenzene-substituted 2'-Deoxyuridine-containing Oligodeoxynucleotides for Photo-Switching Hybridization - Shohei Mori; Kunihiko Morihiro; Satoshi Obika (Molecules, 2014)
A new photoisomeric nucleoside dUAz bearing an azobenzene group at the C5-position of 2'-deoxyuridine was designed and synthesized. Photoisomerization of dUAz in oligodeoxynucleotides can be achieved rapidly and selectively with 365 nm (forward) and 450 nm (backward) irradiation. Thermal denaturation experiments revealed that dUAz stabilized the duplex in the cis-form and destabilized it in the trans-form with mismatch discrimination ability comparable to thymidine. These results indicate that dUAz could be a powerful material for reversibly manipulating nucleic acid hybridization with spatiotemporal control.